Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1590/s0037-86822005000500001
|View full text |Cite
|
Sign up to set email alerts
|

Índice cronotrópico-metabólico na doença de Chagas

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…Nine articles on ChC reported the general aspects of functional evaluation by maximum tests and their determinants (Table 1). One study 21 demonstrated no difference in VO2peak between groups with dilated ChC and with preserved LVEF. However, the study evaluated VO2peak using the conventional maximum exercise test, which could misreport the result.…”
Section: General Aspects Of Functional Evaluation By Maximal Exercise Testsmentioning
confidence: 97%
“…Nine articles on ChC reported the general aspects of functional evaluation by maximum tests and their determinants (Table 1). One study 21 demonstrated no difference in VO2peak between groups with dilated ChC and with preserved LVEF. However, the study evaluated VO2peak using the conventional maximum exercise test, which could misreport the result.…”
Section: General Aspects Of Functional Evaluation By Maximal Exercise Testsmentioning
confidence: 97%
“…The feasibility of selecting patients at risk of sudden death for a more aggressive treatment based on a VTinduced exercise test has not been assessed. Chronotropic incompetence and an abnormal blood-pressure response can impair the exercise capacity of patients with ChD (3), (34) .…”
Section: Exercise Testmentioning
confidence: 99%
“…However, it is important to understand why such patients without overt left ventricular systolic dysfunction seemed to have reduced capacity to exercise. One putative explanation is the presence of chronotropic incompetence observed in nondilated CHD patients, which is related to both reduced vagal heart variability indexes and reduced exercise duration and estimated VO 2 peak 8,9 . Vagal heart dysfunction can occur even in Chagas disease patients without apparent cardiopathy 10 , but it worsens as the left ventricular function deteriorates with disease progression 11 and may affect exercise ability in patients with non-dilated CHD.…”
mentioning
confidence: 99%